Giant cystadenoma of the floor of the mouth: A case report - Castro, Victor Labres da Silva; Corrêa, Tiago Fernando Aires; Guimarães, Valeriana de Castro; Nery, Gustavo Vasconcelos; Ferreira, João Batista (International Archives of Otorhinolaryngology, 2013)
Introduction: Cystadenoma is an uncommon epithelial neoplasia that arises from the salivary glands. The malignancy can affect structures such as the larynx, nasopharynx, buccal mucosa, and palate. Objective: To describe a case of a giant cystadenoma of the floor of the mouth treated at a public hospital in midwestern Brazil. Case report: The patient was a 46-year-old woman with complaints of difficulties in articulating words and swallowing solid food and vocal fatigue. The progression of the disease since the initial consultation, the results of clinical examinations, and the outcome of surgery are described. Finals Comments: Cystadenoma must be considered in the differential diagnosis of cystic injuries in the floor of the mouth if the patient's symptoms are suggestive of this malignancy.
Keywords: salivary glands; minor; mouth; mouth mucosa; exocrine glands